Teacher Perception in Teaching English for SMP in Klaten Regency During Covid-19 Outbreak - Astuti, Mentari; Solikhah, Imroatus (Center of Language and Cultural Studies [CLCS], 2021)
This study explores teacher perception of teaching English using the online system and describes how teacher prepares to teach objectives, teaching materials, teaching methods, and evaluation process for SMP students. This study applies a case study design with a quantitative approach. A number of 22 SMP English teachers in Klaten were recruited as participants of the study. Data were collected using a checklist through the virtual Focus Group Discussion. Basically, data were analyzed using descriptive statistics that present the rate percentage and diagram. Results show in general teachers perceive that online teaching is not prospectively viewed from students’ perspectives. Based on the curriculum planning, teaching objectives are perceived to teach knowledge competence through reading and listening, and skill competence through writing and speaking. Teaching materials are developed based on the 2013 Curriculum and syllabus by relying on online teaching materials. The teaching method is basically based on Google meet and Google classroom. In addition, evaluation is mainly done through Google form, and subsequently paper-based task but submitted online.